Beach Voluntrip sebagai Implementasi Pariwisata Berkalanjutan (Studi Kasus Magang Merdeka Angkatan ke-3 di PT Gemilang Media Wisatama) - Shidqi, Khairu Farras (Jurnal Abdimas Pariwisata, 2024)
Beach Voluntrip as an Implementation of Sustainable Tourism (Case Study of the 3rd Batch of Independent Internships at PT Gemilang Media Wisatama) Volunteer Tourism / Volunteer Tourism / Volunteer-based tourism is the empowerment and development of community-based tourism in which there is an element of tourist involvement to actively contribute to the development of tourism with the ability and social spirit. In line with Voluntourism activities, PT Gemilang Media Wisatama (Travelxism) has a special interest in tourism products initiated by batch 3 MBKM students, namely Beach Voluntrip. The Beach Voluntrip activity has been held twice by PT Gemilang Media Wisata (Travelxism) with the theme "Travel while Protecting the Earth". In the beginning and post-activity processes, tourists, in this case participants, are given two e-forms to fill in their data and feedback. Furthermore, the e-form filled out by the participants is recapitulated to be used as an evaluation of the development of future activities. The development of the Beach Voluntrip special interest tour package lasts 4 months, which includes planning, administrative preparation, and implementation of Beach Voluntrip 1 and 2.